Development of a Competency-Based Evaluation Instrument for Assessing Employability Skills in Good Manufacturing Practices Training - Malika, Febi Fatia; Rayendra, Rayendra; Bentri, Alwen; Alfahani, Khairul (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop a competency-based evaluation instrument for assessing employability skills in GMP training. The study was motivated by the limitation of conventional GMP evaluation instruments that mainly measure technical knowledge and procedural compliance, while providing limited evidence of participants’ ability to apply critical thinking, professionalism, communication, and teamwork in workplace-based situations. This study employed a DDR approach using the Needham model, which consisted of needs analysis, design and development, and evaluation. The instrument was developed by aligning GMP competency standards, employability skill indicators, cognitive levels, and item formats. The final prototype consisted of 20 items, including 10 multiple-choice items and 10 true-false items. Data were collected through expert validation and product testing with GMP training participants at the AGAVI Institute. The data were analyzed using the Gregory Index, KR-20 reliability test, item difficulty analysis, discrimination power analysis, and distractor effectiveness analysis. The results showed that the material validation obtained a Gregory index of 0.73, categorized as high validity, while the evaluation design validation obtained a Gregory index of 0.80, categorized as very high validity. The reliability coefficient was 0.63, indicating acceptable internal consistency for preliminary use. Item analysis showed that most items were easy, with limited discrimination power and distractor effectiveness. Therefore, the instrument is feasible as a validated prototype, although broader testing is needed to strengthen its psychometric stability.